Pemanfaatan Urin Kelinci Sebagai Pupuk Organik Cair untuk Meningkatkan Pertumbuhan dan Hasil Tanaman Cabai Keriting (Capsicum Annuum L.) - Hulopi, Fauzia; Kamaruddin, Kamaruddin; Ode, Asmi (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
The purpose of the study is to determine the optimal concentration of rabbit urine administration (POC Rabbit Urine) to increase the growth and yield of curly chili plants (Capsicum annum L.). This type of research is experimental research. This research was carried out in the Experimental Garden of the Faculty of Agriculture, Unidar Ambon, at an altitude of 150 m above sea level, the average daily temperature is around 27-290C. The experiment will be carried out from February to May 2024. Variables observed on growth components and plant yield components include, plant height, number of leaves, the number of branches, when flowers appear, the number of harvested fruits, the total weight of the fruit of the plant. Observations are made after the plants are 1 week old after planting. The data obtained was analyzed using a variety fingerprint (F test) at the level of 5%. If the real influence is continued, the Smallest Real Difference Test (BNT) is continued. The results showed that the POC treatment of rabbit urine had a real effect on the control of all observed variables. Rabbit urine concentration of 300 ml/L of water resulted in the highest number of harvested fruits and fruit weight compared to other treatments.